Protection of Children’s Rights in Post-Divorce Custody Decisions: A Socio-Legal Analysis of Case No. 0461/Pdt.G/2020/PA Gresik - Salma Elsa Anindya; Atik Winanti (Universitas Nurul Jadid, 2025)
This study examines the regulation of child custody after divorce in Indonesia, focusing on the legal dynamics arising from the general provisions of Article 105 letter (a) of the Compilation of Islamic Law (KHI) which tends to grant custody to the mother, imagining it as the best interest of the child. The problem in this study is how legal provisions in Indonesia regulate the granting of custody to the father after divorce, and the judge's legal considerations in the Gresik Religious Court Decision Number 0461/Pdt.G/2020/PA.Gs consider the best interests of the child. This study uses a Normative Juridical research type with a regulatory, case, and conceptual approach. The data analysis technique used is descriptive qualitative. This shows that custody of the three children, including those who are not yet mumayyiz, is given to the father because the mother is proven to have committed verbal and physical violence. The judge specifically Article 105 letter (a) of the KHI and adheres to Article 4 of Law No. 35 of 2014 concerning Child Protection. This decision is also based on the father's capabilities in psychological, moral, religious, and economic aspects. This study aims to analyze the legal basis and judicial reasoning for granting custody to fathers post-divorce in Indonesia, using a normative juridical method with statutory and case approaches. The findings reveal that the court prioritized the child’s holistic welfare over maternal presumption under Article 105(a) KHI. The study contributes to strengthening the interpretation of child protection law consistent with the principle of the best interests of the child.